Direitos Humanos e Relações Cívico-Militares: o caso da expansão da competência da Justiça Militar no Brasil | Human Rights and Civil-Military Relations: the case of the expansion of the Military Justice Jurisdiction in Brazil - del Rio, Andrés; Cesario Alvim Gomes, Juliana (Mural Internacional, 2020)
O presente artigo analisa a expansão da competência da Justiça Militar no Brasil em casos envolvendo civis e suas consequências para os direitos humanos a partir do contexto de expansão da presença militar na América Latina e da jurisprudência da Corte Interamericana de Direitos Humanos. O artigo examina o caso da Chacina do Salgueiro e alerta para os riscos do incremento do desequilíbrio das relações cívico-militares no país. Palavras-chave: Justiça Militar; Direitos Humanos; América Latina. ABSTRACT The article analyzes the expansion of the competence of the Military Justice in Brazil in cases involving civilians. It calls attention to the consequences of this process for human rights in a context of expanding military presence in Latin America and under the jurisprudence of the Inter-American Court of Human Rights. The article illustrates with the case of the Favela do Salgueiro slaughter and warns of the risks of increasing the imbalance of civic-military relations in the country. Keywords: Military justice; Human Rights; Latin America. Recebido em 02 mar. 2020 | Aceito em 01 set. 2020.